Late early Paleozoic continental collision on the northern margin of the Central Qilian Block, NE Tibetan Plateau: Evidence from a two-stage tectono–metamorphic event. (1st July 2022) - Sun, Yi; Niu, Manlan; Yan, Zhen; Palin, Richard M.; Li, Chen; Li, Xiucai; Yuan, Xiaoyu
Graphical abstract: Highlights: The Central Qilian Block (CQB) experienced HT/MP metamorphism at 450 Ma. The dextral ductile shearing in the CQB developed under low temperature conditions. Continental collision caused HT/MP metamorphism and ductile shearing in the CQB. Abstract: The central part of the Qilian orogenic belt (QOB) on the NE Tibetan Plateau is known as the Central Qilian Block (CQB), and research on deformation and metamorphism of CQB improves our understanding of the tectonic evolution of the QOB, which makes up an important part of the continental crust in eastern Asia. Here we present the results of thermobarometric calculation and geochronological analyses for deformed metamorphic rocks on the northern margin of the CQB, and these new datasets provide a record of the continental collision of the CQB. Macrostructures and microstructures indicate that the CQB underwent dextral ductile deformation. C-axis fabrics and dynamic recrystallisation of quartz indicate that deformation took place at temperatures of 400–500 °C. In contrast, phase equilibrium modelling suggests that the region underwent HT–MP metamorphism along a clockwise P–T path, with peak conditions of ∼ 740 °C and ∼ 7.2 kbar. Zircon U–Pb ages obtained from the zircon rims indicate the HT–MP metamorphism took place at 452–449 Ma. The results of petrographic analyses indicate changes in the rims of the garnet porphyroblasts due to late ductile deformation, which suggests that the ductile shearing took place after the HT–MP metamorphism. The records of different temperatures of metamorphism and deformation are consistent with multi-stage metamorphism–deformation. Together with the results of previous research on the metamorphism, magmatism, and deformation in the CQB, our new datasets confirm that the HT–MP metamorphism and ductile deformation of the CQB were developed during the collision of the CQB and the Alxa Block.